Evaluating Checklist Use in Companion Animal Wellness Visits in a Veterinary Teaching Hospital: A Preliminary Study - Nappier, Michael T.; Corrigan, Virginia K.; Bartl-Wilson, Lara E.; Freeman, Mark; Werre, Stephen; Tempel, Eric (Frontiers in Veterinary Science, 2017)
The number of companion animal wellness visits in private practice has been decreasing, and one important factor cited is the lack of effective communication between veterinarians and pet owners regarding the importance of preventive care. Checklists have been widely used in many fields, and are especially useful in areas where a complex task must be completed with multiple small steps, or when cognitive fatigue is evident. The use of checklists in veterinary medical education has not yet been thoroughly evaluated as a potential strategy to improve communication with pet owners regarding preventive care. The authors explored whether the use of a checklist based on the AAHA/AVMA canine and feline preventive care guidelines would benefit senior veterinary students in accomplishing more complete canine and feline wellness visits. A group of students using provided checklists was compared to a control group of students who did not use checklists on the basis of their medical record notes from the visits. The students using the checklists were routinely more complete in several areas of a wellness visit versus those who did not use the checklists. However, neither group of students routinely discussed follow up care recommendations such as frequency or timing of follow up visits. The study authors recommend considering checklist use for teaching and implementing wellness in companion animal primary care veterinary clinical teaching settings.